Soil acidification in the semiarid regions of North America's Great Plains. Issue 2 (21st March 2019) - Jones, Clain; Engel, Rick; Olson-Rutz, Kathrin
Abstract : Very acidic soil pH conditions have begun to appear in crop fields throughout the semi‐arid regions of the Great Plains. This is, in part, due to N fertilization. Sound N fertilizer and residue management and tailored crop rotations can slow down and prevent soil acidification. Earn 0.5 CEUs in Soil & Water Management by reading this article and taking the quiz at www.certifiedcropadviser.org/education/classroom/classes/680 .